Energy monitoring and load control. application for an off-grid pv system - Ronay Karoly; Bică Dorin; Dumitru Cristian (Scientific Bulletin of the ''Petru Maior" University of Tîrgu Mureș, 2014)
This paper describes the energy monitoring and load control processes as an important part of a renewable energy management system. The main objective of the work is to design a management system for a commercial off-grid consumer that uses solar and biomass energy and to present the monitoring and control processes of this system. The proposed method for this work is to use a micro-controller for the measuring of electrical and other non-electrical parameters of the system, to process the data and to adapt a control process to the technological procedure. The monitoring and control processes are implemented locally on a PC, or from a web application. With this approach an optimal and efficient management system can be adapted for new or existing systems by following and optimizing the technical processes for economic and energy efficiency.